Identify the Usability of the Netraku Application System Using the Usability Testing Method - Dewi, Alifa Permata; Sari, Amarria Dila; Iryani, Devina Inayah; Akhyari, Muhammad Wafa (International Journal of Artificial Intelligence Research, 2024)
The Netraku application is aimed at the visually impaired who want to know the name of an object or the writing of an object or printed media, as well as knowing the nominal currency conveyed via voice in the application. The application works by pointing the camera at the object or currency you want to see the name or amount of. The Netraku application will detect it, and a voice will appear stating the information you want to convey. The problem found is that the Netraku application has not carried out usability testing for blind users. Therefore, it is necessary to develop usability testing to obtain user needs from the Netraku application, determine the effectiveness and efficiency values, and provide recommendations that can be applied to the Netraku application. The methods used in usability testing are performance measurement, focus group discussion, and participatory design. The results obtained on the effectiveness value received a success rate of 83.33% and a failure rate of 16.7%, concluding that the user can complete the task effectively. The efficiency value obtained from the average processing time is 10.34 seconds.